Conductive properties of solid solutions Na3????2xFe2????xNbx(PO4)3 (x = 0 1:5) - Ushchapivska, T. I.; Zatovsky, I. V.; Slobodyanik, M. S.; Kuzmin, R. M. (Reports of the National Academy of Sciences of Ukraine, 2016)
Solid solutions of the NASICON-type with the general formula Na3−2xFe2−xNbx(PO4)3 (x = = 0 ÷ 1.5) have been obtained by the solid state synthesis. The dependence of the conductivity on the temperature (temperature range 323–833 K) of the synthesized compounds has been established. In the temperature range 393–663 К, the conductivity activation energy increases with decreasing the amount of sodium in the composition of the solid solution. The presence of a sodium content limit in the framework has been established to define the maximum value of ionic conductivity.